MEMAKNAI PRIBAHASA BUGIS â€œMAKKALU DAPURENG WEKKA PITUâ€ DALAM HUKUM ISLAM - Hasri, Muammar; Maharani, Erzi Aurelia; M.H, Mustafa (IAIN BONE, 2025)
This article was written based on the famous Bugis Bone proverb